Nanowire formation and polymer conformations of electropolymerized poly(3,4-ethylenedioxythiophene)(PEDOT)on iodine-modfied Au(111) single crystal electrode as probed by in-situ STM - Lapitan, Lorico DS., Jr (Transactions of the National Academy of Science and Technology, 2011)
In the field of nanotechnology, there is a growing interest in the synthesis of conjugated polymer nanowires because of their promising applications in nanodevices and molecular electronics. In this study, the electrochemical polymerization of 3,4-ethylenedioxythiophene (EDOT) (Eox = 1.20 V) on iodine-modified Au(111) single crystal electrode in aqueous 0.10 M HCIO4 was investigated by cyclic voltammetry (CV) and electrochemical scanning tunneling microscopy (EC-STM). The Au(111) single crystal electrode was fabricated using the Clavilier's method. The iodine adlayer was prepared by dipping a freshly annealed Au(111) single crystal electrode in a 0.10 M potassium iodide (KI) solution. Cyclic voltammetric and EC-STM data revealed the iodine adlayer was stable from E = 0.0 - 1.40 V vs. Reversible Hydrogen Electrode. This provided a suitable potential range for EDOT electropolymerization at 1.20 V vs. RHE. EC-STM was used to examine the formation of EDOT adlayer on iodine-modified Au(111) electrode. The iodine adatoms on Au(111) surface were prominent at negative potentials but EDOT molecules gradually appeared as bright spots when the potential was shifted more positively. However, the formation of an ordered adlayer of EDOT molecules was not observed. In-situ electropolymerization of EDOT was carried out at 1.20 V and showed the formation of single-molecular chains of PEDOT with diameter and lengths of 0.9 mm and 5-7 nm respectively. Extensive STM imaging further revealed PEDOT having bended polymer backbones of 105°, 144° and 180° (i.e hairpin folding). The growth of PEDOT multi-layers is observed when the potential was held for a longer time.